Are the available data from laboratory spray burners suitable for CFD modelling validations? A review. (December 2022) - Brito Lopes, A.V.; Emekwuru, N.; Joshi, K.
Abstract: A systematic compilation and evaluation of turbulent spray flame combustion data acquired from lab-scale spray-burners and CFD models validated with these are presented. Previous review studies have been limited to presentations of the progress with validation targets and modelling methods. This work expands these by presenting the details of lab-scale spray-burners and the characteristics of their datasets, the computational methodologies developed to capture the turbulent spray combustion processes acquired from the burners and their validation with the dataset. Additionally, by critically evaluating the spray and inflow boundary conditions, the reacting and non-reacting features and the main flame characteristics and data, direct correlations between the effectiveness of the dataset from the lab-scale spray burners and the outcomes from the computational methodologies using them for validation are clearly elucidated. The evaluation indicates that the turbulence modelling and validation of the swirling non-reacting flows before the application of the combustion models are important. A better representation of the multi-mode nature and the flame-turbulence-chemistry interactions in the combustion models are required. Also, a clearer experimental presentation of the flame structure and modes would help with the development of the modelling techniques. To plug these research needs, this paper reinforces the importance of developing improved numerical techniques that can be validated by selecting an appropriate lab-scale spray-burner with a robust database. Together these can be used to improve the development of and reduce emissions from combustors burning future green fuels.